Jaylene Hunter

Answered

2022-07-25

Determine: $\frac{5}{6}x+\frac{2}{3}=-\frac{1}{6}x-\frac{5}{3}$

Answer & Explanation

Trace House

Expert

2022-07-26Added 7 answers

Step 1

Add $\frac{1}{6}x$ to both sides:

$\to \frac{1}{6}x+\frac{5}{6}x+\frac{2}{3}\phantom{\rule{0ex}{0ex}}=\frac{1}{6}x-\frac{1}{6}x-\frac{5}{3}$

$\to x+\frac{2}{3}\phantom{\rule{0ex}{0ex}}=-\frac{5}{3}$

Add $-\frac{2}{3}$ ro both sides:

$\to x+\frac{2}{3}-\frac{2}{3}\phantom{\rule{0ex}{0ex}}=-\frac{5}{3}-\frac{2}{3}$

$\to x=-\frac{7}{3}$

Add $\frac{1}{6}x$ to both sides:

$\to \frac{1}{6}x+\frac{5}{6}x+\frac{2}{3}\phantom{\rule{0ex}{0ex}}=\frac{1}{6}x-\frac{1}{6}x-\frac{5}{3}$

$\to x+\frac{2}{3}\phantom{\rule{0ex}{0ex}}=-\frac{5}{3}$

Add $-\frac{2}{3}$ ro both sides:

$\to x+\frac{2}{3}-\frac{2}{3}\phantom{\rule{0ex}{0ex}}=-\frac{5}{3}-\frac{2}{3}$

$\to x=-\frac{7}{3}$

Ciara Rose

Expert

2022-07-27Added 4 answers

Step 1

Get like terms to one side

$\frac{5}{6}x+\frac{1}{6}x\phantom{\rule{0ex}{0ex}}=-\frac{5}{3}-\frac{2}{3}$

Step 2

$\frac{6}{6}x=-\frac{7}{3}$

Step 3

$x=-\frac{7}{3}$

Get like terms to one side

$\frac{5}{6}x+\frac{1}{6}x\phantom{\rule{0ex}{0ex}}=-\frac{5}{3}-\frac{2}{3}$

Step 2

$\frac{6}{6}x=-\frac{7}{3}$

Step 3

$x=-\frac{7}{3}$

Most Popular Questions